KEABSAHAN KUASA MEMBEBANKAN HAK TANGGUNGAN DENGAN SURAT KUASA MEMBEBANKAN HAK TANGGUNGAN YANG DIBUAT OLEH NOTARIS - USMAN, RACHMADI - (Direktorat Jenderal Peraturan Perundang-undang, Kementerian Hukum dan Hak Asasi Manusia, 2020)
The validity of a notary deed as an authentic deed is determined in Article 1 number 1 and Article 38 of Law Number 30/2004 concerning the Position of Notary as amended by Law Number 2 of 2014 and Article 1868 of Burgerlijk Wetboek. This provision requires the authenticity of a notarial deed because the deed was made by or in the presence of a public official, the deed was made in the form and procedure (procedure) and conditions determined by law, and the general official who made the deed has the authority to make the deed concerned. Based on this provision, the Power of Attorney Imposing Mortgage Rights (SKMHT) made before a Notary Public using the SKMHT provided by the land party does not qualify as a Notarial Deed, therefore not making binding force (invalid) as an authentic deed, which is because it was made by officials who are generally not authorized and contain disabilities as authentic deeds. SKMHT contains a defect as an authentic deed because the form of SKMHT is not stipulated by law, it is only determined based on the Regulation of the Minister of Agrarian Affairs / Regulation of the Head of the National Land Agency Number 3 of 1997 concerning Provisions for Implementing Government Regulation Number 24 of 1997 concerning Land Registration as amended by Regulation The Head of the National Land Agency Number 8 of 2012 and its form did not meet the requirements as a notarial deed. Therefore, in accordance with Article 38 of Law Number 30/2004 as amended by Law Number 2 of 2014 and Article 1869 of Burgerlijk Wetboek, such SKMHT deed is only located as a deed under the hand, so it does not have the strength of proof. In connection with that, in order for the authenticity of the power to impose Mortgage Rights (HT) fulfilled, the form of power to charge the HT should be made with a notarial deed by following the form and terms of the notary deed or the form of the SKMHT must be specified in the law.